Optic capture pars plana lensectomy - Lee JE (Dove Medical Press, 2012)
Joo Eun LeeDepartment of Ophthalmology, Inje University College of Medicine, Busan, South KoreaObjective: To describe an optic capture pars plana lensectomy technique.Methods: After core vitrectomy, pars plana lensectomy is performed with preservation of the anterior capsule. Capsulorhexis is performed on the preserved anterior capsule through a 2.8 mm clear corneal incision. An intraocular lens (IOL) is placed in the ciliary sulcus, and then the optic of the IOL is pushed back to the vitreous cavity so that the optic is captured by the surrounding capsulorhexis margin.Results: The captured IOL-capsule diaphragm remained stable during air–fluid exchange and prevented air prolapse to the anterior chamber. IOL stability and a clear visual axis were preserved during the follow-up period.Conclusion: With this modified pars plana lensectomy technique, stable IOL position and clear visual axis can be maintained when a pars plana approach is needed during combined cataract and vitreoretinal surgery.Keywords: lensectomy, optic capture, pars plana lensectomy, vitrectomy